Indicators of the osteoclastogenesis system in men with different clinical types of ankylosing spondylitis - T. A. Raskina; O. A. Pirogova; O. V. Zobnina; G. A. Pintova (Современная ревматология)
Objective: to evaluate the osteoclastogenesis regulatory system – osteoprotegerin/receptor activator of nuclear factor-κβ ligand (OPG/RANKL) system – in men with different clinical types of ankylosing spondylitis (AS).Subjects and methods. The osteoclastogenesis regulatory system was studied in 60 men, including 40 patients diagnosed with AS complying with the 1984 New York criteria and 20 men without AS. RANKL, a major stimulant of osteoclastogenesis, and OPG, a decoy receptor that binds RANKL and, accordingly, blocks osteoclastogenesis, were investigated.Results. It was shown that in the patients with AS, RANKL concentrations were normal and the content of OPG and OPG/RANKL ratio proved to be significantly higher than those in the men without AS. The highest OPG concentrations were recorded in patients with the axial form of this disease, its moderate activity and early X-ray stage. No relationship was found between the level of RANKL and the clinical characteristics of AS; however, there was a tendency to a slight increase in its concentration in patients with extraskeletal manifestations of AS, its high activity, high functional class, and late X-ray stage.Conclusion. The considerable increase in OPG levels and OPG/RANKL ratio was ascertained to be associated to the fact that 94% of the patients with late-stage AS characterized by the presence of numerous syndesmophytes. These changes must be compensatory in response to modestly increased RANKL level and enhanced bone resorption.